Small towns attractiveness for living, working and doing business.: case study the Czech Republic - Jiri Jezek (European Regional Science Association (ERSA), 2011)
The paper deals with attractiveness of small towns (from 3 to 20 thousand inhabitants) in the Czech Republic. It analyses development of the inhabitants of the small towns from the half of the 19th century until nowadays. It deals with their advance change and their role in a settlement system. Attention is also paid to their economic and social transformation after the year 1989 and the paper thinks of their future development. It results not only from the official statistical information (especially from inhabitant statistics), but also from own empirical investigations done in the period 2007 - 2011 within solving the project of the Ministry of regional development of the Czech Republic 'Competitiveness of small towns in the Czech Republic'.
Keywords: 330